A Dance With Dragons - Martin George (New York Bantam Books, 2013)
A Dance with Dragons (A Song of Ice and Fire, Book Five ...A Dance with Dragons (ADD) follows Daenerys Targaryen ruling a volatile Meereen in Essos, struggling with her dragons and enemies, while in Westeros, Jon Snow becomes Lord Commander at the Wall facing wildling threats and betrayal, and Stannis Baratheon fights for the North against the Boltons, navigating treacherous political alliances, all while Tyrion Lannister journeys to find Daenerys, with the overarching story showing the vast scale of conflict and political maneuvering in the "War of the Five Kings" aftermath
Keywords: English- Fiction